Investigation of quad-energy high-rate photon counting for X-ray computed tomography using a cadmium telluride detector. (December 2017) - Matsukiyo, Hiroshi; Sato, Eiichi; Oda, Yasuyuki; Yamaguchi, Satoshi; Sato, Yuichi; Hagiwara, Osahiko; Enomoto, Toshiyuki; Watanabe, Manabu; Kusachi, Shinya
Abstract: To obtain four kinds of tomograms at four different X-ray energy ranges simultaneously, we have constructed a quad-energy (QE) X-ray photon counter with a cadmium telluride (CdTe) detector and four sets of comparators and microcomputers (MCs). X-ray photons are detected using the CdTe detector, and the event pulses produced using amplifiers are sent to four comparators simultaneously to regulate four threshold energies of 20, 33, 50 and 65 keV. Using this counter, the energy ranges are 20–33, 33–50, 50–65 and 65–100 keV; the maximum energy corresponds to the tube voltage. We performed QE computed tomography (QE-CT) at a tube voltage of 100 kV. Using a 0.5-mm-diam lead pinhole, four tomograms were obtained simultaneously at four energy ranges. K-edge CT using iodine and gadolinium media was carried out utilizing two energy ranges of 33–50 and 50–65 keV, respectively. At a tube voltage of 100 kV and a current of 60 μA, the count rate was 15.2 kilocounts per second (kcps), and the minimum count rates after penetrating objects in QE-CT were regulated to approximately 2 kcps by the tube current. Highlights: X-ray counter based on quad-energy-range selection has been constructed. Counter is realized by four-sets of comparators and microcomputers. Photon energy determination was carried out online using microcomputers. CT was performed for four X-ray energy ranges with high count rates. Iodine and gadolinium K-edge CT was accomplished simultaneously.